2016
DOI: 10.1111/apt.13641
|View full text |Cite
|
Sign up to set email alerts
|

Serologic microbial associated markers can predict Crohn's disease behaviour years before disease diagnosis

Abstract: Summary Background Patients with Crohn's disease (CD) have serologic responses to various microbial antigens. Serologic markers are associated with aggressive forms of disease and can be detected before onset of symptoms. Their utility in pre‐clinical disease or prediction of complicated disease course before diagnosis is unclear. Aim To evaluate the pattern of serologic anti‐microbial antibodies long prior to diagnosis and the subsequent risk of complicated Crohn's disease at diagnosis. Methods Sera from 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
111
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 36 publications
6
111
0
3
Order By: Relevance
“…When investigating a large number of CD families we showed that CD and their first-degree healthy relatives (FDR) were more frequently colonized with C. albicans than control populations and in FDR the so far unexplained higher prevalence of ASCA with regard to control populations (30%) was associated with the carriage of C. albicans [31] In these studies, C. albicans represented 76–81% of the yeast species isolated compared to only 2–4% for S. cerevisiae . This increase in Candida abundance during CD in contrast with a reduction in S. cerevisiae revealed by culture methods was recently confirmed through NGS micro-mycobiome analysis by two independent groups [4,5]. Thus, the involvement of S. cerevisiae in CD is not supported by epidemiological, pathophysiological or immunological arguments, nor by the unconfirmed correlation between ASCA and UA.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…When investigating a large number of CD families we showed that CD and their first-degree healthy relatives (FDR) were more frequently colonized with C. albicans than control populations and in FDR the so far unexplained higher prevalence of ASCA with regard to control populations (30%) was associated with the carriage of C. albicans [31] In these studies, C. albicans represented 76–81% of the yeast species isolated compared to only 2–4% for S. cerevisiae . This increase in Candida abundance during CD in contrast with a reduction in S. cerevisiae revealed by culture methods was recently confirmed through NGS micro-mycobiome analysis by two independent groups [4,5]. Thus, the involvement of S. cerevisiae in CD is not supported by epidemiological, pathophysiological or immunological arguments, nor by the unconfirmed correlation between ASCA and UA.…”
mentioning
confidence: 88%
“…The number of antigenic targets and the magnitude of the response, are indicative of disease severity [3], are now taken into account when defining the nature of initial treatment[4]. Similarly, their pre-existence to CD onset is increasingly considered in surveys of high risk populations[5]. Despite their widespread use, the mechanisms of generation and persistence of these antibodies remain unknown.…”
mentioning
confidence: 99%
“…Follow-up of people at risk in a longitudinal mode led to the identification of bacterial strains presence/absence and of microbiota diversity modifications as predictors of chronic disease onset or aggravation, as illustrated in Type 1 diabetes, systemic lupus erythematosus (SLE), Crohn's disease, cancers or food allergies [59][60][61][62][63][64]. Here also, monitoring may lead to preventive care measures, adaptation of clinical management and discovery of novel therapies by microbiota modifiers.…”
Section: Metagenomic Analysismentioning
confidence: 99%
“…This study, and two other smaller studies, have shown the presence of serological markers before clinical diagnosis. [4][5][6] Choung et al present novel data to show that the gradual accumulation of serological markers over several years is associated with complications at, or soon after, clinical diagnosis. 6 This observation shows that Crohn's disease has an extended pre-clinical period, perhaps for 5-10 years.…”
mentioning
confidence: 99%
“…[4][5][6] Choung et al present novel data to show that the gradual accumulation of serological markers over several years is associated with complications at, or soon after, clinical diagnosis. 6 This observation shows that Crohn's disease has an extended pre-clinical period, perhaps for 5-10 years. Over this time, there is gradual immune dysregulation and loss of tolerance of the gut immune system to normal microbiological flora.…”
mentioning
confidence: 99%